New organocatalyst derived from abietic acid and 4-hydroxy-L-proline for direct asymmetric aldol reactions in aqueous media - Bhowmick, Sudipto; Kunte, Sunita S.; Bhowmick, Kartick C. (Tetrahedron-Asymmetry, 2014)
Enantioselective direct aldol reactions were carried out in aqueous media with a new organocatalyst that was derived from 4-hydroxy-L-proline and abietic acid via a simple and convenient synthetic protocol with a high overall yield (75%). The new organocatalyst was used for aldol reactions between substituted aromatic aldehydes and various ketones in the presence of several acid additives in aqueous media. The corresponding aldol products were obtained in high isolated yields (up to 99%) and with high anti-diastereoselectivities (up to 94%) and enantioselectivities (>99.9%). The catalyst loading can be efficiently reduced to only 1 mol %. The aldol reactions were found to be extremely fast which is very unusual in organocatalyzed reactions in water. (C) 2014 Elsevier Ltd. All rights reserved.